World Market of Credit Derivatives: Problems of Development and Regulation - Gorbunova, O.A.; Ignatova, O.V.; Tereshina, O.Yu. (Journal of Reviews on Global Economics, 2018)
The article substantiates the authors approach to the definition of credit derivatives. The analysis of development and functioning of the world market of credit default swaps is conducted. The problems of regulation of the world market of credit derivatives are revealed and ways of their solution are suggested.